Success rate of artificial insemination using sexed semen in dairy cows at the Setia Kawan dairy farmers cooperative, Pasuruan, Indonesia - Tsaniya Atikahani Shabirah; Tri Wahyu Suprayogi; Tita Damayanti Lestari; Tatik Hernawati; Rimayanti Rimayanti; Sri Hidanah (Ovozoa: Journal of Animal Reproduction, 2025)
This study aimed to evaluate the success rate of artificial insemination (AI) using sexed semen in dairy cows, based on the parameters of services per conception (S/C), conception rate (CR), and calf sex ratio. A descriptive method was employed, utilizing both primary and secondary data. Primary data were collected through structured interviews with farmers using questionnaires, while secondary data were obtained from institutional records of the Setia Kawan dairy farmers cooperative, located in Tutur District, Pasuruan Regency, East Java, Indonesia. A total sample of 250 dairy cows was selected, representing 15% of the 1,669 cows that had undergone AI with sexed semen. All sampled cows had at least one prior calving and were owned by members of the cooperative, with AI performed between 2021 and 2022. Artificial insemination was conducted by certified inseminators with over five years of experience, within 6-12 hours of estrus detection. The results showed an S/C value of 1.308 (327 inseminations for 250 cows) and a CR of 81.60% (204 pregnancies from 250 inseminations). Of the 250 calves born, 85.2% (213) were female and 14.8% (37) were male, resulting in a female-to-male sex ratio of 5.76:1. These findings suggest that AI using sexed semen can significantly improve both reproductive efficiency and the production of female offspring in dairy herds.